Unexplained - Allen, Judy. (New York : Kingfisher, 2006)
Examines legends and mysteries that challenge human capacity for belief, including hauntings, parapsychology, superstitions, UFOs, and much more.
Includes index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
Library Media Connection, March 2007.
School Library Journal, December 2006.
Keywords: Curiosities and wonders -- Encyclopedias, Juvenile; Parapsychology -- Encyclopedias, Juvenile; Curiosities and wonders -- Encyclopedias; Parapsychology -- Encyclopedias; Curiosities and wonders -- Encyclopedias; Parapsychology -- Encyclopedias